The disease burden of Multiple Sclerosis from the individual and population perspective: Which symptoms matter most? - Barin, Laura; Salmen, Anke; Disanto, Giulio; Babačić, Haris; Calabrese, Pasquale; Chan, Andrew; Kamm, Christian P.; Kesselring, Jürg; Kuhle, Jens; Gobbi, Claudio; Pot, Caroline; Puhan, Milo A.; et al. (Multiple sclerosis and related disorders, 2018)
•Depending on the disease course, quality of life is affected by different symptoms.•For RRMS, gait and balance problems, and fatigue affect most quality of life.•For progressive MS, spasticity and paralysis affect most quality of life.•When measuring with a visual analogue scale, different symptoms gain importance. MS symptoms affect many functional domains. Knowing the specific impact of symptoms on health-related quality of life (HRQoL) is vital for successful disease and symptom management in MS. We aimed at investigating how specific MS symptoms contribute to the disease burden in individuals and from a population perspective. We included 855 Swiss Multiple Sclerosis Registry participants with a relapsing-remitting form (RRMS) or a progressive form (PMS). HRQoL was measured with the EuroQol 5-Dimension EQ-5D-index and EQ-Visual Analogue Scale (EQ-VAS) on 0–100% scales. Their associations with 20 symptoms, socio-demographic and clinical information were explored in median regression models, stratified by RRMS and PMS. We included 611 participants with RRMS and 244 with PMS. In RRMS, gait (−6.5%) and balance problems (−5.1%) had the largest EQ-5D-index reductions, and were also important at the population level (frequencies 45% and 52%). Fatigue, depression, and spasticity (frequencies 74.1%, 31%, 38%) also contributed to the population disease burden. In PMS, spasticity, paralysis, and bowel problems had the largest impact on EQ-5D-index, both at the individual and population levels. The largest impact on EQ-VAS at population level was associated in RRMS with balance problems, depression, dizziness, and spasticity, while in PMS with weakness, pain, and paralysis. While HRQoL at population level is most affected by balance problems, spasticity, and depression in RRMS, the biggest HRQoL losses in PMS are caused by spasticity, paralysis, weakness, and pain. Many symptoms with the largest effects in individuals substantially contribute to the population disease burden.